Expression of Nuclear Factor – kappa B (NF-kB) in Human Breast Cancer Stem Cells (CD 24-/CD 44+) Treated with H2O2 and Its Relationship with Cell Viability - Hendrik Kurniawan; Septelia Inawati Wanandi; Sri Widia A Jusman (Jurnal Kedokteran Meditek, 2023)
Introduction: Breast cancer is one of the highest causes of death from cancer in women in Indonesia. This is partly due to the resistance of ROS-based therapies such as radiotherapy and chemotherapy. Breast cancer stem cells (cancer stem cells, CSCs) have a role in this resistance mechanism. Previous studies demonstrated the ability of CSC to survive oxidative stress conditions due to rotenone administration. Therefore, in this study an analysis was carried out on the transcription factor NF-kB in breast cancer cells, both CSCs and Non CSCs, related to the role of NF-kB in maintaining the survival of cancer cells under conditions of oxidative stress. Methods: The study was conducted on human breast cancer stem cells (CD24-/CD44+) and non stem cells (CD24-/CD44-) which were given H2O2 at concentrations of 1.1µM, 11µM, and 110µM with control cells not given H2O2. Assessment was carried out on the parameters of NF-kB mRNA expression, and cell viability.  Results: Administration of H2O2 at a concentration of 11µM showed a significant increase in the expression of NFk-B CSCs mRNA compared to non CSCs (p<0.05). As for the viability test results, at all concentrations of H2O2 it appears that CSCs was able to maintain its viability compared to non CSCs which experienced a decrease in viability (p<0.05). Conclusion: In this study, conditions of oxidative stress due to the administration of H2O2 led to an increase in the expression of NF-kB mRNA in CSCs so that cell viability could be maintained.